2014
DOI: 10.1097/bor.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti inflammatory drugs, glucocorticoids and disease modifying anti-rheumatic drugs for the management of rheumatoid arthritis before and during pregnancy

Abstract: Although NSAIDs are well tolerated for use during the first two trimesters of pregnancy, they should be avoided during a conception cycle so as not to impede implantation. After gestational week 30, these medications should be discontinued as they may cause premature closure of the ductus arteriosus. The nonfluorinated glucocorticoids, prednisone and prednisolone, can be used throughout pregnancy, although use during the first trimester may increase the risk of cleft palate formation. Protracted glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 66 publications
0
41
0
1
Order By: Relevance
“…In addition to the known risks associated with glucocorticoids, in particular hypertension and diabetes, their use during the first trimester also increases the risk of cleft palate formation by 2–3 fold, although the absolute risk is still considered low, with baseline risk of approximately 1/1000 live births [106,107]. A meta-analysis of 10 studies observed over a 30+ year time period revealed a non-significant increase in risk of major malformations associated with in utero exposure [107].…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…In addition to the known risks associated with glucocorticoids, in particular hypertension and diabetes, their use during the first trimester also increases the risk of cleft palate formation by 2–3 fold, although the absolute risk is still considered low, with baseline risk of approximately 1/1000 live births [106,107]. A meta-analysis of 10 studies observed over a 30+ year time period revealed a non-significant increase in risk of major malformations associated with in utero exposure [107].…”
Section: Medications During Autoimmune Ctd Pregnanciesmentioning
confidence: 99%
“…Although the association between the use of prednisone during pregnancy and an increase of oral clefts is controversial, the use of prednisone is not considered to be teratogenic in general [87,93]. During pregnancy, glucocorticoids may exert the same side effects as outside of pregnancy, which might be more damaging during pregnancy, like insulin resistance.…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…During pregnancy, glucocorticoids may exert the same side effects as outside of pregnancy, which might be more damaging during pregnancy, like insulin resistance. Furthermore, of relevance for pregnancy, the use of corticosteroids has been associated with intrauterine growth restriction, shorter gestational age [43], premature rupture of the membranes, and longer TTP [9,87,93].…”
Section: Glucocorticosteroidsmentioning
confidence: 99%
“…Evidence‐based guidelines to assist clinicians in making this analysis are lacking, and compared with the abundant literature on managing pain during labor, there is limited information on pain management during gestation. Because of ethical concerns, safety data for analgesic use in pregnancy is largely limited to animal studies or observational studies in humans, and thus may be confounded by selection bias, and exposure or outcome misclassification . Many obstetric studies also have methodological issues, such as low recruitment rates and inadequate sample sizes, which may limit their feasibility and external validity .…”
Section: Introductionmentioning
confidence: 99%